Decision support system for game selection / Muhammad Haykal Mohamad Hithir - Mohamad Hithir, Muhammad Haykal (2015)
Games have been in our life throughout human history and it is still evolving. With the technology that we have now, games are becoming more interesting to play with than before. But then, with too many games to choose from, gamers have problems in choosing the suitable and fun games for them to play with. This indecisive decision is becoming more challenging for new gamers. Purchasing a non-interesting game is such a waste of money and time. Thus, this project develops a decision support prototype that assists gamers in selecting the suitable games based on the type and genre of the games. The construction of the rules for decision making is provided by an expert in games. The method that is being used in this project is rule-based expert system. Since human is always uncertain with their selections, Certainty Factor is integrated in this prototype where it accepts user’s uncertain decision and it is being transformed into ambiguous word that is associated with the decision making. This project can be improve to obtain more accurate result. The choice and the parameter given to the user can be added more so that user can answer them with more detail and specific what kind of game that they really interested.